Intestinal Haemorrhage and Colitis Induced by Treatment With Osimertinib for Non-Small-Cell Lung Carcinoma: A Case Report - Shujun, Wang; Lili, Lou; Lei, Yang; Feng, Wang; Hefeng, Zhan (Frontiers in Pharmacology, 2022)
Background: Osimertinib is recommended either as the first-line therapy for sensitizing EGFR-mutations (FLAURA trial) or at progression to first-/second-generation EGFR inhibitors in the presence of resistance mutation T790M (AURA 3 study). It can effectively improve the prognosis of patients with NSCLC with manageable adverse reactions. Among adverse events, intestinal haemorrhage is rare and requires extensive study on its potential lethality. Case presentation: A 59-year-old female, diagnosed with relapsed stage IV (cT4N2M1c) NSCLC with T790M mutation of the EGFR gene, received osimertinib treatment. Eight months after osimertinib treatment, she complained of lower abdominal pain and haematochezia without haemorrhoids. Potential causes of intestinal haemorrhage other than osimertinib toxicity were ruled out. Colonoscopy examination showed severe colitis with grade 3 CTCAE. Osimertinib was discontinued, and prednisone 0.5 mg/kg was administered. Follow-up endoscopy showed no pathological findings. A novel third-generation EGFR-TKI, aumolertinib, was administrated. Five months after aumolertinib initiation, CT evaluation showed stable disease (SD), and this patient was free of colitis recurrence. Conclusion: To our knowledge, this is the first case report of severe colitis as an adverse event associated with osimertinib. Although osimertinib is the standard treatment for NSCLC in patients with T790M mutation and has fewer side effects, colitis may occur after months of treatment. Aumolertinib, a novel third-generation EGFR-TKI, might be an effective alternative for the treatment of patients with NSCLC experiencing colitis from osimertinib.